Adolescents’ self-report on the use and helpfulness of stress coping strategies - Orska, Rita; Pigozne, Tamara; Usca, Svetlana (Social Welfare: Interdisciplinary Approach, 2018)
The article presents the results of the first stage of the Latvia-Lithuania cross-border project “Developing of Social Psychological Support Service System through Implementation of Method of Positive Coping Strategies and Enhancement of Social Inclusion for People in Vulnerable Groups” (POZCOPING), in which, based on the adolescents’ self-report and using the methodology (Adolescent Coping Scale) developed by E. Freidenberg and R. Lewis, stress-causing problems and the use and helpfulness of stress coping strategies of adolescents’ in Latvia were identified and analysed.